Examining the overlap in lymphatic filariasis prevalence and malaria insecticide-treated net access-use in endemic Africa. - Joanna L Whisnant; Mustafa Kamal Sikder; Gizachew Taddesse Akalu; Tsegaye Alemu; Mubarek Yesse Ashemo; Amelia Bertozzi-Villa; Annie J Browne; Ewerton Cousin; Paulina Agnieszka Dzianach; Yalemzewod Assefa Gelaw; Peter W Gething; Taren M Gorman; et al. (PLoS Neglected Tropical Diseases, 2025)
Eradication and elimination strategies for lymphatic filariasis (LF) primarily rely on multiple rounds of annual mass drug administration (MDA), but also may benefit from vector control interventions conducted by malaria vector control programs. We aim to examine the overlap in LF prevalence and malaria vector control to identify potential gaps in program coverage. We used previously published geospatial estimates of LF prevalence from the Institute for Health Metrics and Evaluation, as well as publicly available insecticide-treated net (ITN) access (proportion of the total population with access to ITNs) and use (proportion of the total population that slept under an ITN) estimates among the total population and malaria Plasmodium falciparum parasite rates (PfPR) from the Malaria Atlas Project (MAP). We aggregated the 5x5 km2 estimates of LF prevalence estimates and ITN estimates to the implementation unit (IU) level using fractional aggregation, for 33 LF and malaria-endemic locations in Africa, and then overlaid the IU-level aggregates. In this analysis, ITN coverage was low in areas where LF is common, with 51.7% (90/174) of high-LF-prevalence-IUs having both access and use estimates under 40%. Most (67.8%; 61/90) of these low-ITN-coverage, high-LF-prevalence locations were also categorized as high- or highest-prevalence for malaria by PfPR, suggesting suboptimal ITN coverage even in some malaria-co-endemic locations. Even in IUs with high LF prevalence but low malaria prevalence, almost half (48.2%; 39/81) had high levels of access to ITNs. When accounting for population, however, gaps in ITN access in such areas were evident: more individuals lived in high-LF, low-malaria IUs with low ITN access (8.68 million) than lived in high-LF, low-malaria IUs with high ITN access (6.76 million). These results suggest that relying on current malaria vector control programs alone may not provide sufficient ITN coverage for high LF prevalence areas. Opportunities for coordinated vector control programs in places where LF and malaria prevalence are high but ITN coverage is low - or additional ITN distribution in high-LF, low-malaria locations - should be explored to help achieve elimination goals.